Changes in liver function tests in laparoscopic cholecystectomy versus open cholecystectomy in a tertiary care center - Shashank Kumar; Ashika Happy; Shishir Kumar; Dinanath Prasad; Mohammad Eqbal Ahmad (International Journal of Research in Medical Sciences, 2023)
Background: Gallstone disease is a major health problem worldwide particularly in the adult population. The traditional open cholecystectomy (OC) has been replaced by laparoscopic cholecystectomy (LC), with LC becoming the gold standard for management of gall stone disease. Elevation in the levels of liver enzymes following LC is a major cause of concern. Hence the present study determines and compares the changes in liver function tests following Laparoscopic cholecystectomy with open cholecystectomy, as well the significance of these changes is studied. Methods: A total of 100 patients with symptomatic cholelithiasis were selected in the study from October 2020 to October 2022. The cases were randomly divided into two groups, Group LC and Group OC. The blood samples were collected for Liver Function Tests (LFT)-Pre-operatively, Post-operative Day (POD)-1, POD-2 and POD-7 and enzyme alterations were studied. Results: The study demonstrated increase in levels of Serum AST, ALT, ALP in LC group on POD-1 and POD-2 with p<0.001, while the levels returned to reference values on POD-7. In OC group the increase in levels of Serum AST, ALT, ALP were observed on POD-1 only with p<0.05 and the levels returned to normal values by POD-2 of majority of patients. The changes in LFT were higher in LC group compared to OC group (where the changes were slight). Conclusions: Cholecystectomy especially laparoscopic, leads to transient significant hepatic enzyme alterations which can be attributed to CO2 pneumoperitoneum, surgical manipulations, diathermy and arterial injury. These derangements at times may be of concern to surgeons for its implication to the integrity of biliary tract.